Acute effects of blood flow restriction with whole-body vibration on sprint, muscle activation and metabolic accumulation in male sprinters - Zhang, Junjie; Zhou, Ruihang; Zhao, Ningning; Li, Yamei; Liu, Haiyuan; Zhang, Wanxia; Guo, Wenxia (Frontiers in Physiology, 2023)
Purpose: The aim of this study was to explore the acute effects of Blood Flow Restriction Training (BFRT), Whole-Body Vibration (WBV), and BFRT + WBV on the 20m sprint, muscle activation, and metabolic response in male sprinters. Method: Sixteen male sprinters randomly performed BFRT, WBV, or BFRT + WBV interventions with 72h intervals. Before and during each intervention, electromyography (EMG) signals were collected during the intervention, fingertip blood was taken before, immediately after, and 15 minutes after the intervention, and a 20m sprint was performed 3 minutes after the intervention. Results: (1) 0-10m and 0-20m sprint performance were significantly improved after WBV and BFRT + WBV interventions (P < 0.05), 0-20m sprint performance was significantly improved after all three interventions (P < 0.05), with greater benefits after BFRT + WBV intervention. (2) After BFRT + WBV intervention, the EMG amplitude of the lateral femoral muscle and soleus muscle were significantly improved. The electromyography RMS and immediate post-intervention metabolic response of the tibial anterior muscle after the BFRT intervention were significantly higher than those of the BFRT + WBV intervention (P < 0.05). Conclusion: For sprint performance, BFRT and WBV had similar post-activation enhancement effects to BFRT + WBV, and the metabolic responses immediately following the BFRT were higher than that following BFRT+WBV in male sprinters.